1976
DOI: 10.1159/000465568
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of IgG Anti-A and -B Antibody in Old Age

Abstract: The titer of anti-A and -B IgM antibody was tested in 57 sera from patients aged 65 years or more. 31 of these sera were also titered for the occurrence and titer of IgG antibody. All sera were found to have a low titer (2-64) of IgM antibody but 14 sera contained IgG antibody. However, only two of 12 sera with a higher IgM antibody titer (16-64) exhibited the IgG antibody in contrast to 12 of 19 sera with a low titer of IgM antibody (2-4). The difference was statistically significant (p = 0.014).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The fall of these antibody levels in full-adult and senile animals may suggest that aging is associated with the decline of various immune functions including blood group antibody formation. In regard to the immunoglobulin class, Baumgarten, Kruchok and Weirich (1976) found that anti-A and anti-B antibodies of IgG class appeared very frequently in old persons aged 65 years or more. In the present experiment, we demonstrated antibody levels by the indirect Coombs method to detect anti-A and anti-B antibodies of IgG class, frequently demonstrated in the group-O cynomolgus monkey (Terao et al 1983).…”
Section: Discussionmentioning
confidence: 96%
“…The fall of these antibody levels in full-adult and senile animals may suggest that aging is associated with the decline of various immune functions including blood group antibody formation. In regard to the immunoglobulin class, Baumgarten, Kruchok and Weirich (1976) found that anti-A and anti-B antibodies of IgG class appeared very frequently in old persons aged 65 years or more. In the present experiment, we demonstrated antibody levels by the indirect Coombs method to detect anti-A and anti-B antibodies of IgG class, frequently demonstrated in the group-O cynomolgus monkey (Terao et al 1983).…”
Section: Discussionmentioning
confidence: 96%